Biliary reconstruction by isolated jejunal interposition loop: Our experience after excision of choledochal cyst - Somak Krishna Biswas; Kalyani Saha Basu; Sumitra Kumar Biswas; Hinglaj Saha; Subhankar Chakravorty; Jay Kishor Soren (Wolters Kluwer Medknow Publications, 2020)
Background: Choledochal cyst is a fairly common hepatobiliary condition in pediatric surgical practice. For the most common type (type I), it is well established that the total excision of the cyst with an wide biliary-enteric anastomosis is key for long-term good result. Multiple options remain for biliary-enteric reconstruction after excision. Jejunal interposition loop reconstruction is thought to be the most physiologic. Materials and Methods: We have retrospectively reviewed the data of patients of type I choledochal cysts which were operated between January 2010 and September 2018 and undergone jejunal interposition loop reconstruction. Clinical presentation, investigations, operative procedure morbidity and complications were reviewed. Results: There were 33 patients, with a male-to-female ratio of 1:3 and a mean age of 4.63 years (mean ± standard deviation [SD] = 4.63 ± 2.98 years). The follow-up period ranged from 3 to 81 months (mean ± SD = 36.30 ± 19.24 months). There was no stricture or cholangitis. Reoperation required in one due to leak at biliary-enteric anastomosis leading to biliary peritonitis. One each had pancreatitis and prolonged ileus. Two bile leaks stopped spontaneously. Operative time and postoperative hospital stay were 228.78 ± 40.43 min (mean ± SD) and 8.96 ± 3.63 days (mean ± SD), respectively. Conclusion: Jejunal interposition loop reconstruction is safe and reproducible with acceptable morbidity. However, if this procedure is abandoned, the long-term benefits may remain ever elusive.